Homogeneity and universal quanti?cation in embedded questions - Blok, Dominique; Chark, Jordan (Proceedings of Sinn und Bedeutung, 2021)
Based on experiments carried out in three languages (German, Dutch, Ulster English) we provide evidence for the claims that question-internal universal quanti?ers (who all) can be made at-issue and collapse homogeneity in embedded contexts. We show that these question quantifying particles can be accounted for in a domain restriction analysis (Brisson, 2003). Couched within the account of homogeneity provided in Kriz and Spector (2020), homogeneity removal follows as a result of these particles ?attening the alternatives which enter into the computation of homogeneity.